2018
DOI: 10.1097/md.0000000000012829
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chinese herbal medicine Ping Chuan Ke Li for the management of mild/moderate persistent asthma

Abstract: This study assessed the effectiveness and safety of Chinese herbal medicine Ping Chuan Ke Li (PCKL) for the treatment of patients with mild/ moderate persistent asthma.A total of 108 eligible patients with persistent asthma were included and were divided into a treatment group and a control group in this retrospective study. All 108 patients underwent oral montelukast. Additionally, subjects in the treatment group also received PCKL therapy. All patients in both groups were treated for a total of 1 month. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
1
0
3
Order By: Relevance
“…Wang et al [13] e Li et al [14] utilizaram o Ping Chuan Ke Li (PCKL) para o tratamento de asma de seus sujeitos. No trabalho de Li et al [14], após quatro semanas de tratamento com fitoterápico para asma, os pacientes do grupo tratamento não apresentaram melhoras significativas na função pulmonar, bem como na qualidade de vida, comparado com o grupo controle. Os eventos adversos mais frequentes incluíram náusea, tosse e corrimento nasal.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Wang et al [13] e Li et al [14] utilizaram o Ping Chuan Ke Li (PCKL) para o tratamento de asma de seus sujeitos. No trabalho de Li et al [14], após quatro semanas de tratamento com fitoterápico para asma, os pacientes do grupo tratamento não apresentaram melhoras significativas na função pulmonar, bem como na qualidade de vida, comparado com o grupo controle. Os eventos adversos mais frequentes incluíram náusea, tosse e corrimento nasal.…”
Section: Resultsunclassified
“…Além disso, não foram encontradas diferenças nos efeitos adversos entre os grupos. Nosso estudo corrobora os achados de Li et al [14] ao não encontrar melhoras significativas nos testes de função pulmonar, entretanto obtivemos diferença na qualidade de vida, ao contrário deste estudo. Os pacientes do Grupo 2 (Sham) e Grupo 3 (Intervenção) espontaneamente reduziram seus medicamentos, atitude contrária ao que foi solicitado antes do nosso estudo.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Though the exact mechanisms of TCM are still unclear, it has shown some effects in anti-in ammation, airway relaxation, and reducing airway hypersensitivity [31]. TCM, used as adjuvant therapy, can reduce asthma symptoms, enhance patients' lung function, and improve the quality of life, but the treatment effects were limited and may not reduce the risk of exacerbations [31,32]. Our study showed a continuous decrease in TCM use over the years while increasing use of western medicine, which may be explained by the implementation of the guidelines or the limited e cacy of TCM in patients with moderate to severe asthma.…”
Section: Discussionmentioning
confidence: 99%